Accuracy Analysis of Fluid Volume Measurement And Calculation Methods on Multislice Computed Tomography - Widiatmoko, Mahfud Edy; Asumsie Tarigan, Asumsie; Alfian, Indra (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Background: Multislice Computed Tomography (MSCT) is utilized for the measurement of bleeding volume in hemorrhagic stroke patients. This is very necessary to determine the right medical action. Errors in measurement can lead to suboptimal medical measures taken. Objective: to analyze the measurement and calculation of fluid volume by automatic and manual methods on the volume of fluid contained in the phantom on MSCT. Methods: The type of research is quantitative experimental with the sample used is a phantom made of polyethylene (Dacron) filled with irregular milk liquid as much as 10 volume variations. The research instruments used were worksheets and interview sheets. Data processing and analysis are descriptive by getting the average value. Results: Measurement and calculation of irregular volume of 10 ml, 20 ml, 30 ml, 40 ml, 50 ml, 60 ml, 70 ml, 80 ml, 90 ml, and 100 were done automatically on the CT scan plane and manually using the formula ½ A x B x C. The automatic method had an average volume difference of 1.39% and the manual method had an average volume difference of 6.88%. The automatic method has a small volume difference. Conclusion: the measurement and calculation of volume with the automatic method has a better accuracy value than the manual method. The results of these measurements and calculations are highly dependent on the accuracy of precise segmentation techniques on the object.